Tecnologia social e inclusão social: um estudo de caso da Cooperativa Catamare - Bolson, Camille Rossato (2015)
This research has as a central theme the social technologies and social inclusion. Its overall objective was to analyze the potential and limitations of Cooperative CATAMARE as an alternative to the development of social technologies and to promote social inclusion. Become specific objectives of the study an analysis of the productive and organizational process and the socio economic and environmental condition of the cooperatives. To achieve the objectives proposed by the research, the methodology used was a case study with a qualitative approach supported by structured questionnaires, semi-structured interviews and participant observation. The research was developed in three phases: the first one was exploratory, the second phase was descriptive, and the third phase was analytic, since the responses obtained from the interviews will be interpreted and analyzed in an integrated manner to the information obtained in non-participant observation. The relevance of this initiative is the possibility of expanding the understanding of the processes of development of social technologies and the institutional environment that develops from these experiences. Among the results it was found that, although membership of the cooperative has improved the social, economic and political condition of members, there are still structural limits of the production chain of recycling and organizational development that hampering progress towards the development of social technologies and the social inclusion of the waste pickers from CATAMARE.